THE COLOR PATTERN OF ALABIO DUCK (Anas platyrhynchos Borneo) IN SOUTH KALIMANTAN - Suryana, S.; Noor, R.R.; Hardjosworo, P.S.; Prasetyo, L.H. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The study was carried to identify the phenotypic variation of Alabio duck (Anas platyrhynchosBorneo) being kept by smallholder. This research was conducted in Hulu Sungai Selatan (HSS), HuluSungai Tengah (HST) and Hulu Sungai Utara (HSU), South Kalimantan from May until November2009. Six hundreds (75 males and 525 females) duck characterized in this study was age ranged from5-5.5 months old. The observed parameters were plumage color, color feature, plumage shine, the colorof bill, feet and shank. The results showed that the ducks from three locations (HSS, HST and HSU)performed different plumage color and color feature. The dominant plumage color of the Alabio maleduck was grayish white on the neck (44-56%), grayish black on the back (40-60%) brownish grey onthe chest (52-80%), while the wing was more dominated by blue-green (56%) and black (80%) in thetail. Whereas the female ducks was dominated (70-100%) brown spotted color, the rest blackish gray attail, such as back, neck and chest. Twinkle Alabio duck plumage on males and females have the highestpercentage was the glint of silver (100%) and of shiny blue-green for males (85-100%). The percentageof phenotypic color of bill, feet and shank of male and female ducks were lite yellow (40-60%), brightorange (12-44%), pale yellow (8-28%) and black (4-12%).